Scintigraphic Imaging of The Upper Urinary System - Çiftçi, İsmail; Balcı, Tansel Ansal (Fırat University, 2003)
In general, Nuclear Medicine techniques give information about the functional and in part morphological status of the organs and tissues. Different tissues may be imaged with respect to the characteristics of the radiopharmaceutical agent. Renal scintigraphies allow the quantitation of the renal blood flow, glomerular, tubular and drainage functions, and to evaluate the cortical structure of kidneys, effectively and non invasively. Tc-99m DTPA and Tc-99m DMSA are the most commonly used radiopharmaceuticals for renal imaging. We aimed to give a general information about renal scintigraphy in this paper.

Nükleer Tıp yöntemleri genel olarak organ ve dokuların fonksiyonel durumu hakkında bilgi verir. Kullanılan radyofarmasötik ajanın özelliklerine göre farklı dokular görüntülenebilir. Sintigrafik metodlarla, böbreklerin perfüzyon, konsantrasyon ve drenaj fonksiyonları ile kortikal bütünlüğünün değerlendirilmesi de noninvaziv ve efektif bir şekilde yapılabilir. Tc-99m DTPA ve Tc-99m DMSA böbrek görüntülemesinde en sık kullanılan radyofarmasötiklerin başında gelmektedir. Yazımızda, böbrek sintigrafisi ile ilgili genel bir bilgi vermeyi amaçladık.
Üst Üriner Sistemin Sintigrafik Görüntülemesi